Peculiarities of Real Educational Institutions Functioning in the Subcarpathian Rus (Pidkarpatska Rus) - Safyanyuk, Zoryana (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The article highlights historical and pedagogical aspects of the development of real secondary educational institutions that functioned in the territory of the Subcarpathian Rus (1919- 1939). After World War I the Czechoslovak Republic undertook a commitment to arrange Transcarpathia as an administrative unit entitled the “Subcarpathian Rus”. The situation with Ukrainian schools in the Subcarpathian Rus was very poor. Only two town schools were Ukrainian. In spite of the language chaos in the land, Rus (Ukrainian) town schools started to be set up and Hungarian ones started being re-organized. In the 20ies – 30ies in the Subcarpathian Rus as there appeared real national secondary schools (real grammar schools) in which students were mainly Ukrainians. In real grammar schools with their utilitarian nature of the content of education there could be traced the growth in the number of students due to improved access to those institutions. However, gradually, the trend towards Czechization could be traced, a number of forms with Czech as the language of teaching were opened. The Academy of Sciences in Prague, having researched the language issue, decided that the language the “Subcarpathian Rus people” were speaking was identical to the Ukrainian language of the Halychyna people, therefore Ukrainian was acknowledged to be the language of teaching at Ukrainian real grammar schools. All in all, as of 1933 Ukrainian real grammar schools in Berehovo, Khust, Mukachevo and Uzhhorod had 46 forms, parallel Czech units in Khust, Mukachevo and Uzhhorod had 20 forms, parallel Hungarian units in Berehovo had 12 forms, the reformed Jewish grammar school in Mukachevo had 8 forms. In total there were 9 secondary schools.